2006
DOI: 10.1016/j.phytochem.2006.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Bafoudiosbulbins A, and B, two anti-salmonellal clerodane diterpenoids from Dioscorea bulbifera L. var sativa

Abstract: Two clerodane diterpenoids, Bafoudiosbulbins A 1, and B 2, together with five known compounds: tetracosanoic acid, 1-(tetracosanoyl)-glycerol, trans-tetracosanylferulate, b-sitosterol and 3-O-b-D-glucopyranosyl-b-sitosterol were isolated from the tubers of Dioscorea bulbifera L. var sativa. Their structures were established by spectroscopic methods (1D and 2D-NMR, MS) and X-ray crystallographic diffraction analysis of compound 1. The CH 2 Cl 2 -soluble portion of the crude extract and the two clerodanes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 19 publications
1
69
0
Order By: Relevance
“…52 D. bulbifera tubers are known to contain various bioactive compounds, including flavonoids, terpenoids, phenanthrenes, amino acids, protein, and glycosides. [53][54][55][56][57][58][59] It is speculated that the alcohol groups are oxidized to carbonyl groups in the course of reduction, which supports the suggestion that polyol groups are primarily responsible for the bioreduction process. Thus, the water-soluble fractions of D. bulbifera played key roles in the bioreduction of the precursors and evolution of shape in the nanoparticles.…”
Section: Discussionmentioning
confidence: 69%
“…52 D. bulbifera tubers are known to contain various bioactive compounds, including flavonoids, terpenoids, phenanthrenes, amino acids, protein, and glycosides. [53][54][55][56][57][58][59] It is speculated that the alcohol groups are oxidized to carbonyl groups in the course of reduction, which supports the suggestion that polyol groups are primarily responsible for the bioreduction process. Thus, the water-soluble fractions of D. bulbifera played key roles in the bioreduction of the precursors and evolution of shape in the nanoparticles.…”
Section: Discussionmentioning
confidence: 69%
“…It is already known that silver nanoparticles in the aqueous solution are defined by an absorption spectrum in the range of 400 to 450 nm (Zargar et al 2011). It was also suggested that frequency and width of the surface plasmon resonance (SPR) absorption are correlated with the morphology and size of the nanoparticles (Teponno et al 2006). The morphological characterization was achieved through scanning electron microscopy ( Figure 3).…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…It is also used in the treatment of carbuncles, lung abscesses, breast lumps, and goiter (Gao et al, 2003). In addition, DB displays a range of pharmacological properties, including antitumor (Grynberg et al, 1999), antifeedant (Cifuente et al, 2002), antiinflammation (Demetzos et al, 2001), and antisalmonellal activities (Teponno et al, 2006). DB and related remedies are used for the treatment of thyroid gland diseases and varieties of tumors (Tang, 1995;Rasikari et al, 2005).…”
Section: Introductionmentioning
confidence: 99%